Genetic variants influencing effectiveness of exercise training programmes in obesity – an overview of human studies - Leońska-Duniec, A; Ahmetov, II; Zmijewski, P (Biology of Sport, 2016)
Frequent and regular physical activity has significant benefits for health, including improvement of body composition and help in weight control. Consequently, promoting training programmes, particularly in those who are genetically predisposed, is a significant step towards controlling the presently increasing epidemic of obesity. Although the physiological responses of the human body to exercise are quite well described, the genetic background of these reactions still remains mostly unknown. This review not only summarizes the current evidence, through a literature review and the results of our studies on the influence of gene variants on the characteristics and range of the body’s adaptive response to training, but also explores research organization problems, future trends, and possibilities. We describe the most reliable candidate genetic markers that are involved in energy balance pathways and body composition changes in response to training programmes, such as FTO, MC4R, ACE, PPARG, LEP, LEPR, ADRB2, and ADRB3. This knowledge can have an enormous impact not only on individualization of exercise programmes to make them more efficient and safer, but also on improved recovery, traumatology, medical care, diet, supplementation and many other areas. Nevertheless, the current studies still represent only the first steps towards a better understanding of the genetic factors that influence obesity-related traits, as well as gene variant x physical activity interactions, so further research is necessary.